Greystone secrets #1 eaudiobook The strangers. - Haddix, Margaret Peterson (Greystone Secrets, 2019)
New York Times bestselling author Margaret Peterson Haddix takes readers on a thrilling adventure filled with mysteries and plot twists aplenty in this absorbing series about family and friendships. Perfect for fans of A Wrinkle in Time and The City of Ember! What makes you you? The Greystone kids thought they knew. Chess has always been the protector over his younger siblings, Emma loves math, and Finn does what Finn does best—acting silly and being adored. They've been a happy family, just the three of them and their mom. But everything changes when reports of three kidnapped children reach the Greystone kids, and they're shocked by the startling similarities between themselves and these complete strangers. The other kids share their same first and middle names. They're the same ages. They even have identical birthdays. Who, exactly, are these strangers? Before Chess, Emma, and Finn can question their mom about it, she takes off on a sudden work trip and leaves them in the care of Ms. Morales and her daughter, Natalie. But puzzling clues left behind lead to complex codes, hidden rooms, and a dangerous secret that will turn their world upside down. Praise for The Strangers: ""A secret-stacked, thrilling series opener about perception, personal memories, and the idiosyncrasies that form individual identities."" (Publishers Weekly, starred review) * Winter 2018–2019 Kids' Indie Next List Pick * Indie Bestseller * Time for Kids Book Club: Top 10 Summer Reads * PW Best Books 2019 * Texas Bluebonnet Award List 2020-2021 * 2020 LITA Excellence in Children's and Young Adult Science Fiction Notable Book: The Eleanor Cameron Notable Middle Grade Books List *